PRAKTIK FATHERLESS DAN KAITANNYA DENGAN PENGASUHAN ANAK DALAM FIKIH ISLAM DAN HUKUM PERKAWINAN DI INDONESIA - Wahab, Abdul; Alfarisi, Usman; Susandra, Nurbayu; Fajriyanthi, Nurul Aulia (Mitsaqan Ghalizan, 2024)
The phenomenon of fatherless, which is increasingly prevalent in Indonesia, has become a serious concern due to its negative impact on children’s development, both physically, mentally, and spiritually. This study aims to analyze the perspective of Islamic Fiqh and the Marriage Law regarding the role of fathers in child care, identify the father’s obligations in child care according to Islamic Fiqh and the Marriage Law, and determine the impact of fatherless practices on child growth. This study uses a library research method with a qualitative approach. The data used are primary data and secondary data obtained from various sources of literature, such as books, journals, and official documents. Data collection techniques were carried out through literature studies, and data analysis used content analysis. The results of the study show that Islamic Fiqh and the Marriage Law in Indonesia both emphasize the importance of the father’s role in child care. Fathers have an obligation to provide sustenance, educate and guide children, as well as provide affection and attention. However, fatherless practices in Indonesia are caused by several factors, such as high divorce rates, unbalanced parenting patterns, patriarchal culture, and the death of the father. The impact of fatherless on children’s growth and development can be in the form of father hunger, which is a condition of psychological damage that results in low self-esteem, difficulty adapting, slow psychological maturity, difficulty managing emotions, and lack of decision-making ability.